Treatment needs and impact of oral health screening of athletes with intellectual disability in Belgium. Issue 1 (December 2015) - Fernandez, C; Declerck, D; Dedecker, M; Marks, L
Abstract Background Special Olympics Special Smiles (SOSS) is an initiative created for oral health data collection and education in oral hygiene for athletes with an intellectual disability. The aims of this study were to evaluate treatment needs of participants of Special Olympics in Belgium 2013 in comparison with those from 2008 and to assess the impact of screening and referral within the SOSS in a group of athletes who participated in two consecutive events, 2012 and 2013. Methods Data were collected following a standardized protocol developed by the U.S. Centres for Disease Control and Prevention, Division of Oral Health. Oral hygiene habits, treatment urgency and reports of oral pain, gingival signs, sealants, untreated caries, missing and filled teeth were recorded. Data analysis of data from 2013 consisted in descriptive statistics followed by the analysis of the data by univariable and multivariable logistic regression. This data was compared with data from 2008 published by Leroy et al., 2012 using Chi square tests. Data from athletes who participated in both Special Olympics events (2012 and 2013) were compared using Exact McNemar's test and Chi-square test for homogeneity of proportions. The level of significance for all tests was set at a p-value < 0.05. Results A total of 627 athletes with intellectual disability participated to the SOSS program in 2013, while 132 athletes met the inclusion criteria of being a participant at both SO Belgium 2012 and 2013. The prevalence of gingival signs was 44.3 % in 2013, slightly higher than in 2008 (42.4 %). The burden of untreated decay affected 27.1 % of the population showing a net increase in comparison to 2008 (20.9 %). McNemar's test and Chi-square test revealed that there were no statistically significant differences in the proportions of all compared parameters between 2012 and 2013. Conclusion Special Olympics results from 2013 indicate a considerable unmet treatment need among Belgian Special Olympics Athletes, persistent from 2008 to 2013. Moreover, SO intervention had no impact in the oral health of athletes who participated in 2012 and 2013 events. Continuous efforts for preventive and restorative oral health care are needed for this population.